Who wants to hire a more diverse faculty? A conjoint analysis of faculty and student preferences for gender and racial/ethnic diversity. (26th May 2020) - Carey, John M.; Carman, Kevin R.; Clayton, Katherine P.; Horiuchi, Yusaku; Htun, Mala; Ortiz, Brittany
ABSTRACT: What explains the scarcity of women and under-represented minorities among university faculty relative to their share of Ph.D. recipients? Among many potential explanations, we focus on the "demand" side of faculty diversity. Using fully randomized conjoint analysis, we explore patterns of support for, and resistance to, the hiring of faculty candidates from different social groups at two large public universities in the U.S. We find that faculty are strongly supportive of diversity: holding other attributes of (hypothetical) candidates constant, for example, faculty at both universities are between 11 and 21 percentage points more likely to prefer a Hispanic, black, or Native American candidate to a white one. Furthermore, preferences for diversity in faculty hiring are stronger among faculty than among students. These results suggest that the primary reason for the lack of diversity among faculty is not a lack of desire to hire them, but the accumulation of implicit and institutionalized biases, and their related consequences, at later stages in the pipeline.